Determination of the structure of y-alumina using empirical and first principle calculations combined with supporting experiments - Paglia, Gianluca (Curtin University, 2004)
Aluminas have had some form of chemical and industrial use throughout history. For little over a century corundum (α-Al2O3) has been the most widely used and known of the aluminas. The emerging metastable aluminas, including the γ, δ, η, θ, κ, β, and χ polymorphs, have been growing in importance. In particular, γ-Al2O3 has received wide attention, with established use as a catalyst and catalyst support, and growing application in wear abrasives, structural composites, and as part of burner systems in miniature power supplies. It is also growing in importance as part of the feedstock for aluminium production in order to affect both the adsorption of hydrogen fluoride and the feedstock solubility in the electrolytic solution. However, much ambiguity surrounds the precise structure of γ-Al2O3. Without proper knowledge of the structure, understanding the properties, dynamics and applications will always be less than optimal. The aim of this research was to contribute towards settling this ambiguity. This work was achieved through extensive computer simulations of the structure, based on interatomic potentials with refinements of promising structures using density functional theory (DFT), and a wide range of supporting experiments. In addition to providing a more realistic representation of the structure, this research has also served to advance knowledge of the evolution of the structure with changing temperature and make new insights regarding the location of hydrogen in γ-Al2O3.Both the molecular modelling and Rietveld refinements of neutron diffraction data showed that the traditional cubic spinel-based structure models, based on m Fd3 space group symmetry, do not accurately describe the defect structure of γ-Al2O3. A more accurate description of the structure was provided using supercells of the cubic and tetragonal unit cells with a significant number of cations on c symmetry positions. These c symmetry based structures exhibited diffraction patterns that were characteristic of γ-Al2O3. The first three chapters of this Thesis provide a review of the literature. Chapter One provides a general introduction, describing the uses and importance of the aluminas and the problems associated with determining the structure of γ-Al2O3. Chapter Two details the research that has been conducted on the structure of vi γ-Al2O3 historically. Chapter Three describes the major principles behind the computational methods employed in this research. In Chapter Four, the specific experimental and computational techniques used to investigate the structure of γ-Al2O3 are described. All preparation conditions and parameters used are provided. Chapter Five describes the methodology employed in computational and experimental research. The examination of the ~ 1.47 billion spinel-based structural possibilities of γ-Al2O3, described using supercells, and the selection of ~ 122,000 candidates for computer simulation, is detailed. This chapter also contains a case study of the structure of κ-Al2O3, used to investigate the applicability of applying interatomic potentials to solving complex structures, where many possibilities are involved, and to develop a systematic procedure of computational investigation that could be applied to γ-Al2O3. Chapters Six to Nine present and discuss the results from the experimental studies.Preliminary heating trials, performed to determine the appropriate preparation conditions for obtaining a highly crystalline boehmite precursor and an appropriate calcination procedure for the systematic study of γ-Al2O3, were presented in Chapter Six. Chapter Seven details the investigation of the structure from a singletemperature case. Several known structural models were investigated, including the possibility of a dual-phase model and the inclusion of hydrogen in the structure. It was demonstrated that an accurate structural model cannot be achieved for γ-Al2O3 if the cations are restricted to spinel positions. It was also found that electron diffraction patterns, typical for γ-Al2O3, could be indexed according to the I41/amd space group, which is a maximal subgroup of m Fd3 . Two models were presented which describe the structure more accurately; Cubic-16c, which describes cubic γ-Al2O3 and Tetragonal-8c, which describes tetragonal γ-Al2O3. The latter model was found to be a better description for the γ-Al2O3 samples studied. Chapter Eight describes the evolution of the structure with changing calcination temperature. Tetragonal γ-Al2O3 was found to be present between 450 and 750 °C. The structure showed a reduction in the tetragonal distortion with increasing temperature but at no stage was cubic γ-Al2O3 obtained. Examination of the progress of cation migration indicates the reduction in the tetragonal nature is due to ordering within inter-skeletal oxygen layers of the unit cell, left over from the breakdown of the hydroxide layers of boehmite when the transformation to γ-Al2O3 occurred. Above 750 °C, δ-Al2O3 was not observed, but a new phase was identified and designated γ.-Al2O3.The structure of this phase was determined to be a triple cell of γ-Al2O3 and is herein described using the 2 4m P space group. Chapter Nine investigates the presence of hydrogen in the structure of γ-Al2O3. It was concluded that γ-Al2O3 derived from highly crystalline boehmite has a relatively well ordered bulk crystalline structure which contains no interstitial hydrogen and that hydrogen-containing species are located at the surface and within amorphous regions, which are located in the vicinity of pores. Expectedly, the specific surface area was found to decrease with increasing calcination temperature. This trend occurred concurrently with an increase in the mean pore and crystallite size and a reduction in the amount of hydrogen-containing species within the structure. It was also demonstrated that γ-Al2O3 derived from highly crystalline boehmite has a significantly higher surface area than expected, attributed to the presence of nano-pores and closed porosity. The results from the computational study are presented and discussed in Chapter Ten. Optimisation of the spinel-based structural models showed that structures with some non-spinel site occupancy were more energetically favourable. However, none of the structural models exhibited a configuration close to those determined from the experimental studies. Nor did any of the theoretical structures yield a diffraction pattern that was characteristic of γ-Al2O3. This discrepancy between the simulated and real structures means that the spinel-based starting structure models are not close enough to the true structure of γ-Al2O3 to facilitate the derivation of its representative configuration.Large numbers of structures demonstrate migration of cations to c symmetry positions, providing strong evidence that c symmetry positions are inherent in the structure. This supports the Cubic-16c and Tetragonal-8c structure models presented in Chapter Seven and suggests that these models are universal for crystalline γ-Al2O3. Optimisation of c symmetry based structures, with starting configurations based on the experimental findings, resulted in simulated diffraction patterns that were characteristic of γ-Al2O3.